Kandungan Nitrat dan Fosfat pada Air Sungai Yeh Ho Tabanan, Bali - Prasat, Lasmana; Perwira, Ima Yudha; Pebriani, Dewa Ayu Angga (Current Trends in Aquatic Science, 2022)
This study aimed to determine the value of nitrate, phosphate, and the quality state of the water in the Yeh Ho river Tabanan Regency Bali based on the Government Regulation Number 22/2021. This research was conducted at 3 different location (upstream as station 1, middle stream as station 1, and downstream as station 3) of the Yeh Ho River (Tabanan, Bali) during February 2021. Water sample was analyzed for nitrate, phosphate, and the other water quality parameters (pH, temperature, and DO). Nitrate was measured using KIT Salifert Nitrate, phosphate was measured using KIT Hanna HI713, pH was measured using pH meter, water temperature was measured using thermometer, and DO was measured using DO meter. The result showed that nitrate in the water of Yeh Ho river was ranging from 0.25 to 0.29 mg/L, while phosphate was ranging from 0.10 to0.19 mg/L. The average value of pH, temperature, and DO in the water were: 6,95 mg/L, 27,15 o C, and 5,2  mg/L, respectively. This result indicates that nitrate and phosphate value in the water of Yeh Ho river is belong to Class II and III which can be used for aquaculture and recreational use.